PEMERINTAHAN YANG CERDAS YANG DIBUTUHKAN DALAM REVOLUSI INDUSTRI 4.O - Redjo, Samugyo Ibnu (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Komputer Indonesia, 2019)
The future government is a digital government that relies on the ability of E. Govt. (electronicgovernment) and it is impossible to avoid it. Advances in science, communication technology andinformation and the development of the economy and trade. Cause the Government is faced with anincreasingly liberal and individualist mass of people who tend to deny the existence and grandeur ofculture and religion. It is also necessary to understand that the social transformation experienced by